PERAN UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN DALAM MEMODERASI PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS - Oktapiani, Ni Luh Made Wiwiek; Wiksuana, I Gusti Bagus (E-Jurnal Manajemen; Vol 7 No 3 (2018)DO - 10.24843/EJMUNUD.2018.v7.i03.p03, 2018)
This study aims to determine the effect of capital structure on profitability and to know the ability of firm size and sales growth in moderating the influence of capital structure on profitability. This study uses quantitative approach is associative. This research is located at mining company in Indonesia Stock Exchange period 2012 - 2016 with population of 42 companies and samples used amounted to 25 companies. The analysis technique in this research is moderate regression analysis (MRA). Based on the classical assumption test shows the result that the regression model used is correct. Result of research by using regression analysis of moderation indicate that there is positive influence between capital structure to profitability. Firm size is able to moderate the effect of capital structure on profitability but sales growth is not able to moderate the effect of capital structure on profitability. Keywords: capital structure, profitability, firm size, sales growth.